2021
DOI: 10.1177/09589287211035701
|View full text |Cite
|
Sign up to set email alerts
|

How can we become more equal? Public policies and parents’ work–family preferences in Germany

Abstract: This study examines how public policies affect parents’ preferences for a more egalitarian division of paid and unpaid work. Based on the assumption that individuals develop their preferences within a specific policy context, we examine how changes in three policies affect mothers’ and fathers’ work–family preferences: the availability of high-quality, affordable childcare; the right to return to a full-time job after having reduced hours to part-time and an increase in the number of ‘partner months’ in parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…The rather modest strength of the priming effects on normative judgments regarding parental leave usage of mothers and fathers is in line with previous priming survey experiments regarding family policies more generally (Bünning and Hipp 2022; Pedulla and Thébaud 2015) and is probably attributable partly to the fact that our priming information was very short. Providing more detailed and more interactive information might encourage more reflection and yield stronger effects.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The rather modest strength of the priming effects on normative judgments regarding parental leave usage of mothers and fathers is in line with previous priming survey experiments regarding family policies more generally (Bünning and Hipp 2022; Pedulla and Thébaud 2015) and is probably attributable partly to the fact that our priming information was very short. Providing more detailed and more interactive information might encourage more reflection and yield stronger effects.…”
Section: Discussionsupporting
confidence: 86%
“…When receiving the priming, women more often preferred egalitarian work–care arrangements, whereas men’s preferences were affected only if they believed that their male peers also preferred gender-egalitarian arrangements (Pedulla and Thébaud 2015; Thébaud and Pedulla 2016). Recently, Bünning and Hipp (2022) showed that in the context of a hypothetical increase in the individual and nontransferrable paid parental leave entitlement from 2 to 4 months in Germany, fathers increased their preferred leave length, whereas mothers preferred shorter leaves. By examining specific, existing family policies and related scientific evidence on consequences of leave taking instead of hypothetical family policy contexts, our study offers a novel, yet policy- and practice-relevant extension to our understanding of norm-setting effects of policies.…”
Section: Theoretical Background and Previous Evidence On Normative Po...mentioning
confidence: 99%
“…This mechanism can be called priming. Survey experiments from the United States and Germany have investigated how priming with hypothetical family policy improvements may change work–care preferences of the potential target population (Thébaud and Pedulla, 2016; Pedulla and Thébaud, 2015; Bünning and Hipp, 2022). Thébaud and Pedulla (2016) analysed the effect of priming with hypothetical policies supporting the reconciliation of employment and family care on the preferred future work–family arrangements of young childless adults in the United States.…”
Section: Normative Policy Feedback: Theory and Previous Evidence On T...mentioning
confidence: 99%
“…For men, supportive work–family policies only had an impact when they believed that other men also preferred gender-egalitarian relationships (Thébaud and Pedulla, 2016). For Germany, Bünning and Hipp (2022) tested, as one of three hypothetical policy scenarios, how priming with greater availability of high-quality affordable day care affected working hours preferences among parents with young children. The authors found that mothers would want to work slightly longer hours in the presence of greater day care availability.…”
Section: Normative Policy Feedback: Theory and Previous Evidence On T...mentioning
confidence: 99%
See 1 more Smart Citation